Muscle-tendon unit length changes in knee extensors and flexors during alpine skiing - Alhammoud, M.; Racinais, S.; Dorel, S.; Guilhem, G.; Hautier, C. A.; Morel, B. (Sports Biomechanics, 2024)
This study characterised the thigh muscle-tendon unit length variations (MTUv) in elite alpine skiing. MTUv were modelled for seven muscles from knee and hip angles in 17 national team skiers during 1602 cycles (546 Slalom (SL), 908 Giant-Slalom (GS), 136 Super-Giant (SG) and 12 Downhill (DH) cycles). The biarticular rectus femoris showed a dynamic pattern on both legs, especially in SL. On the other side, vastii displayed a stable length on the inside leg in all disciplines (37-46% of the cycle), contrasting with their dynamic behaviour on the outside leg being quasi-static for only 3% (SL) to 27% (DH) of the cycle. SL showed the largest amplitude of MTUv followed by GS, SG and DH. For vastus lateralis, MTUv was ~60%Lr./s in SL but only ~12%Lr./s in DH. In SL, a fine desynchronisation between both joints led to nearly constant MTUv (slow lengthening lasting ~45-51% of the cycle) for the biarticular hamstrings separated by faster variations during turn switch from outside to inside leg. In summary, biarticular MTUv were not characterised by single-joint behaviours, suggesting that extrapolating contraction regimen from knee joint only is not accurate in alpine skiing.